The tension of writing across the curriculum, a subservient and subversive curricular movement - Norwood-Klingstedt, Matthew, author; Doe, Sue R., advisor; Carter, Genesea M., committee member; Aragon, Antonette, committee member (Colorado State University. Libraries, 2020)
A Writing Across the Curriculum Program (or proponent or article) that does not seek to transform the classroom into a locus of consciousness-raising and liberating education is not one that is in keeping with the original intentions of WAC because it, along with Writing Studies and Rhetoric and Composition, has traditionally worked towards a more socially just academy. Antiracism is of paramount importance to the field of Rhetoric and Composition and, specifically, WAC because engaging in discussions of racial and language diversity is central to the objectives of writing instruction and consistent with the social justice aims of the field of Rhetoric and Composition. The question of whose language is valued and accepted—and, therefore, who is promoted and valued—is at the heart of all these curricular movements. To fail to make strides towards the integration of antiracist pedagogy and theory with WAC is a failure to listen to students and to anticipate their needs. I found that two of the most well-known and regarded WAC-focused journals, The WAC Journal and Across the Disciplines, show a lack of focus on antiracist pedagogy and theory. It appears as though, at least when looking at articles written for these publications from 2015-2019, current scholarship does not create space for antiracist educational pedagogy and theory. Based on the silence surrounding the topic within WAC-focused publications, there seems to be a sort of willful naivety within WAC with regards to social justice. WAC is not considering how it might integrate antiracism within its main publications. To provide an example of a journal that does create space for antiracist educational pedagogy and theory and to ensure my methodological tool could be applied, I selected four articles from Research in the Teaching of English that lent themselves to comparative analysis. Because antiracism is a fundamental shift in how to teach, who to value, what to value, and the way to present ourselves, I make three recommendations for WAC scholars that immediately move to integrate antiracism.
Keywords: composition; social change; writing across the curriculum; rhetoric; antiracism; WAC